The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24020915
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Oxidative Stress, Neuroinflammation and Abnormal Myelination in Excessive Aggression Associated with Depression: Recent Input from Mechanistic Studies

Abstract: Aggression and deficient cognitive control problems are widespread in psychiatric disorders, including major depressive disorder (MDD). These abnormalities are known to contribute significantly to the accompanying functional impairment and the global burden of disease. Progress in the development of targeted treatments of excessive aggression and accompanying symptoms has been limited, and there exists a major unmet need to develop more efficacious treatments for depressed patients. Due to the complex nature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 298 publications
(322 reference statements)
2
16
0
2
Order By: Relevance
“…The present study demonstrated that chronic exposure to unpredictably alternating ultrasound frequencies, that are naturally emitted by rodents to communicate with conspecifics, is capable of inducing depressive syndrome in female mice, associated with systemic pro-inflammatory changes, and eliciting behavioral deficits in offspring. The present data are in accordance with earlier demonstrated findings in males that 21 days of exposure of BALB/c mice to unpredictably alternating frequencies of ultrasound between the ranges of 20-25 and 25-45 Hz led to decreased sucrose intake, a sign of anhedonia in rodents and increased anxiety-like behavior, as shown by decreased time spent in the center of the open field and open arms in the elevated plus maze [29,37]. Notably, here we demonstrated that ultrasound exposure causes pro-inflammatory changes locally in the hippocampus of dams and systemically in the blood, suggesting a profound pro-inflammatory effect of ultrasound stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study demonstrated that chronic exposure to unpredictably alternating ultrasound frequencies, that are naturally emitted by rodents to communicate with conspecifics, is capable of inducing depressive syndrome in female mice, associated with systemic pro-inflammatory changes, and eliciting behavioral deficits in offspring. The present data are in accordance with earlier demonstrated findings in males that 21 days of exposure of BALB/c mice to unpredictably alternating frequencies of ultrasound between the ranges of 20-25 and 25-45 Hz led to decreased sucrose intake, a sign of anhedonia in rodents and increased anxiety-like behavior, as shown by decreased time spent in the center of the open field and open arms in the elevated plus maze [29,37]. Notably, here we demonstrated that ultrasound exposure causes pro-inflammatory changes locally in the hippocampus of dams and systemically in the blood, suggesting a profound pro-inflammatory effect of ultrasound stress.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the overexpression of GSK-3β in the hippocampus, that we revealed in pregnant dams, is known to be a marker of distress and depressive syndrome [42]. In this paper, we report an over-expression of GSK-3β, IL-1β, and IL-6 mRNA in the hippocampus of ultrasound-exposed females, which is similar to the changes found in males [29,30,37].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Brain tissue is extremely high in oxygen consumption and has weak antioxidant capacity. Brain cell membranes are abundant in lipid components, contain a large number of metal ions, and are important sites for oxidative stress 44,45 . An elevated TyG index significantly exacerbates oxidative stress, which produces large amounts of free radicals that can damage brain tissue, eventually leading to depression 46–48 .…”
Section: Discussionmentioning
confidence: 99%
“…Brain cell membranes are abundant in lipid components, contain a large number of metal ions, and are important sites for oxidative stress. 44,45 An elevated TyG index significantly exacerbates oxidative stress, which produces large amounts of free radicals that can damage brain tissue, eventually leading to depression. [46][47][48] In addition, oxidative stress can damage the structure and function of mitochondria, which subsequently leads to impairment of the mitochondrial respiratory chain, reduction of ATP synthesis, and disruption of cellular energy metabolism.…”
Section: Discussionmentioning
confidence: 99%